Web based LIS education: potentials and feasibility of regional models - Petr, Kornelija (Array, 2002)
Distance education has been attracting the attention of library associations and educators for more than 60 years, and even more since the advent of the Internet. The paper discusses the application of distance education in Croatia for the LIS Continuing Professional Development.